2012
DOI: 10.1021/jp307896c
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Diphenylacetylene: Light from the “Dark State”

Abstract: A weak band at the tail of the known tolane (diphenylacetylene, DPA) fluorescence spectrum in several solvents is assigned to the forbidden 1(1)A(u) → 1(1)A(g) transition on the basis of its lifetime (∼200 ps) and its fluorescence excitation spectra. The 1(1)A(u) state, generally called the dark state, is not truly dark. We report the temperature (T) dependence of DPA fluorescence quantum yields (ϕ(f)) in methylcyclohexane (MCH) solution and the fluorescence and phosphorescence quantum yields of DPA in glassy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 92 publications
6
48
1
Order By: Relevance
“…This excited‐state scenario, in which both a linear “bright” π–π* state and a trans‐bent “dark” π–σ* state are located on the S 1 potential energy surface, resembles those already investigated for diphenylacetylene and for other organic molecules with C≡X (X=C or N) groups . However, in the present case, we did not succeed in finding a minimum for the trans‐bent π–σ* state of 2 since TD‐DFT optimizations failed.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This excited‐state scenario, in which both a linear “bright” π–π* state and a trans‐bent “dark” π–σ* state are located on the S 1 potential energy surface, resembles those already investigated for diphenylacetylene and for other organic molecules with C≡X (X=C or N) groups . However, in the present case, we did not succeed in finding a minimum for the trans‐bent π–σ* state of 2 since TD‐DFT optimizations failed.…”
Section: Resultssupporting
confidence: 80%
“…Accordingly, the corresponding dyads can adopt a large number of virtually isoenergetic conformations, which are generated by the reciprocal orientations of the optimal dihedral angles between the different moieties of the dyads (Tables S1–S7). While the tolane unit in known to be planar, the biphenyl one is displays torsional angles of about 40°, depending on the environment . As a consequence, the dihedral angle between the plane of the carbazole and of the terpyridine moiety ( i. e ., α DA in Table ) can vary substantially within the different minima of a specific dyad, ranging from nearly coplanar to almost perpendicular conformations (as in the simplest case of 1 , see Table , Table S1 and Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…They found that while the lowest‐energy singlet state of diphenylacetylene is the 1B 1u (ππ*) state in the linear D 2h symmetry, the πσ* state of the 1 1 Au symmetry in the bent C 2h symmetry is the lowest in energy. The transition from fluorescent ππ* state to weakly fluorescent πσ* state required crossing a small energy barrier [15] . The prediction arising from the calculation were confirmed experimentaly [26,31,32,33] .…”
Section: Introductionsupporting
confidence: 69%
“…Emission from the "dark" state (1 1 A u → 1 1 A g ) is weak due to its bent, stilbene-like structure. 20 The triplet state (1 3 B 1u ) is linear with a lifetime of τ = 1 μs. 21−23 Tolanes twist either through sterically demanding groups 15,24−32 or by choosing a suitable tether, connecting the two phenyl rings.…”
Section: ■ Introductionmentioning
confidence: 99%